Remote creative processes in the theater: Stanislavski's Active Analysis and RPG (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
This paper investigates methodological procedures used to create a virtual theater play, based on Stanislavski's active analysis and elements of RPG (role playing games). It discusses theoretical concepts, describes methodological choices, and, in conclusion, reflects upon the creative process in a remote context. This reflection intends to emphasize that, even though the experience of virtual theater does not equate with live theater, virtual theater has the potential to be more than a remedial production alternative in the context of a pandemic, aggregating formal possibilities within the great array of experiences that we understand as contemporary theater.
Keywords: Active Analysis; Stanislavski; RPG; Virtual theater